2014
DOI: 10.1254/jphs.13162fp
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Thalidomide Embryotoxicity by In Vitro Embryotoxicity Testing Based on Human iPS Cells

Abstract: Abstract. The mouse embryonic stem cell test (mEST) is used to assess the embryotoxicity of drug candidates by evaluating the effects on the cardiac differentiation of stem cells. However, thalidomide embryotoxicity has not yet been reported using the mEST. To detect the effects of thalidomide, we used human induced pluripotent stem cells (hiPSCs) instead of mouse embryonic stem cells, and assessed three endpoints: the inhibition of cardiac differentiation, the cytotoxicity to hiPSCs, and the cytotoxicity to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…Therefore, simple assays to achieve similar findings are desired, and many in vitro developmental toxicity assays have been developed, such as the mouse embryonic stem cell test (EST) (Annett et al, 2016;Seiler and Spielmann, 2011;Scholz et al, 1999;Genschow et al, 2002Genschow et al, , 2004, zebrafish test (Truong et al, 2011) and devTOX TM test (Palmer et al, 2013) using human embryonic stem cells or human induced pluripotent stem (iPS) cells. We also reported the preliminary method of in vitro iPS cells testing (iPST) (Aikawa et al, 2014) that is a modified version of the EST and a promising animal-free approach.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, simple assays to achieve similar findings are desired, and many in vitro developmental toxicity assays have been developed, such as the mouse embryonic stem cell test (EST) (Annett et al, 2016;Seiler and Spielmann, 2011;Scholz et al, 1999;Genschow et al, 2002Genschow et al, , 2004, zebrafish test (Truong et al, 2011) and devTOX TM test (Palmer et al, 2013) using human embryonic stem cells or human induced pluripotent stem (iPS) cells. We also reported the preliminary method of in vitro iPS cells testing (iPST) (Aikawa et al, 2014) that is a modified version of the EST and a promising animal-free approach.…”
Section: Introductionmentioning
confidence: 99%
“…We sought here to develop an in vitro teratogenicity assay that recapitulates the early stem cell specification events upstream of limb bud development. The gold standard in vitro assay for teratogenicity testing has been the mEST, which measures the influence of putative teratogens on the spontaneous cardiac differentiation of mouse embryoid bodies 20,[51][52][53] . The mEST presents several limitations, namely the subjectivity of analysis, and was characterized as 53-79% accurate for predicting teratogenicity depending on the chemical reference set used 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The mEST presents several limitations, namely the subjectivity of analysis, and was characterized as 53-79% accurate for predicting teratogenicity depending on the chemical reference set used 16,17 . Thalidomide is teratogenic in humans, NHPs, and rabbits but does not induce teratogenicity in mice 1,7 , and indeed the mEST has been appropriately insensitive to the effects of thalidomide, though it is sensitive to the effects of other known mouse and human teratogens including atRA 20 . Recently, an hPSC-based teratogenicity assay of definitive endoderm differentiation was established and characterized as 94% predictive of visceral malformations in preclinical species 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we could not detect the teratogenicity of thalidomide in the mEST. Recently, Aikawa et al (2014) demonstrated the embryonic toxicity of thalidomide (weak teratogenicity) using human induced pluripotent stem cells. Further modification of the protocol might be needed to achieve better predictions in the mEST.…”
Section: Discussionmentioning
confidence: 99%